Assembly of AUF1 with eIF4G–poly(A) binding protein complex suggests a translation function in AU-rich mRNA decay - Lu, Jin-Yu (Cold Spring Harbor Laboratory Press, 2006)
An AU-rich element (ARE) located in the 3′-untranslated region of many short-lived mRNAs functions as an instability determinant for these transcripts. AUF1/hnRNP D, an ARE-binding protein family consisting of four isoforms, promotes rapid decay of ARE-mRNAs. The mechanism by which AUF1 promotes rapid decay of ARE-mRNA is unclear. AUF1 has been shown to form an RNase-resistant complex in cells with the cap-initiation complex and heat shock proteins Hsp70 and Hsc70, as well as other unidentified factors. To understand the function of the AUF1 complex, we have biochemically investigated the association of AUF1 with the components of the translation initiation complex. We used purified recombinant proteins and a synthetic ARE RNA oligonucleotide to determine the hierarchy of protein interactions in vitro and the effect of AUF1 binding to the ARE on the formation of protein complexes. We demonstrate that all four AUF1 protein isoforms bind directly and strongly to initiation factor eIF4G at a C-terminal site regardless of AUF1 interaction with the ARE. AUF1 is shown to directly interact with poly(A) binding protein (PABP), both independently of eIF4G and in a complex with eIF4G. AUF1–PABP interaction is opposed by AUF1 binding to the ARE or Hsp70 heat shock protein. In vivo, AUF1 interaction with PABP does not alter PABP stability. Based on these and other data, we propose a model for the molecular interactions of AUF1 that involves translation-dependent displacement of AUF1–PABP complexes from ARE-mRNAs with possible unmasking of the poly(A) tail.